MSME BUSINESS POLICY STRATEGY: GROBBAK KOREA - Puspita, Tita; Nustiawan, Alyaa Hasna Luthfiyah; Luna, Gaizka Tiara Meisya; Aurelya, Nadhira; Nadif, Muhammad (Univesitas Muhammadiyah Tangerang, 2025)
This study analyzes the business policy strategies of Grobbak Korea, a pioneer of Korean street food in Indonesia, in addressing market dynamics and shifting culinary trends. Using a qualitative descriptive approach, the research evaluates internal factors such as operational capacity, human resources, and financial management, alongside external factors such as industry competition, food trends, and consumer purchasing power. The analysis employs PESTEL, SWOT, Porter’s Five Forces, and TOWS frameworks. The findings indicate that Grobbak Korea benefits significantly from the rising popularity of Korean culture but faces considerable challenges, including operational limitations and dependency on centralized supplies. The study recommends product innovations that incorporate local flavors, community-based marketing strategies, and operational and logistical optimizations to enhance competitiveness and ensure business sustainability.